PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP HASIL BELAJAR SISWA SMP - Nofatin, Nofatin; Sulistyarin, Sulistyarin; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this study was to find out how much influence the used of social media at seven grades of students learning outcomes in social sciences in SMP N 9 Pontianak. There were five indicators such as allocation time for used of social media, the reasons used of social media, the positive impact of social media, the negative impact of social media and types of social media. For indicators of time allocation of the use of social media obtained with an average of 3,78 categorized into very good classification, the reason of used of social media has an average of 3,45 categorized into good classification, positive impact social media has an average of 3,37 categorized into good classification, negative impacts of social media has an average of 3,49 categorized into good classification and for types of social media have an average of 3,5 categorized into good classification and supported by interviews. Based on the technique and data analysis, it was obtained with the same regression namely Y = 19,169 + 0,595X. T test results show that thitung> ttabel (1,620> 0,2042). While the coefficient of determination R2 0,039 means the percentage contribution of the influence of the use of social media with learning outcomes of 0,39% while 0,61% is influenced by other factors that have.Keywords: Use of Social Media, Student Learning Outcomes, Social Studies